Finite-time trajectory control for a quadrotor aircraft using disturbance observer. (2nd April 2020) - Chu, Zhaobi; Zhou, Songgang; Zhu, Min; Li, Hua
In this article, we investigate the problem of finite-time trajectory tracking control for a quadrotor aircraft with unknown external disturbances. To improve convergence rate and disturbance rejection performance, a new composite controller is proposed by integrating finite-time control design and disturbance estimation attenuation technique. Explicit Lyapunov function is given to ensure the finite-time stability of the closed-loop control system. Numerical simulations also show the effectiveness of the proposed method.